In patients with idiopathic pulmonary fibrosis the presence of hiatus hernia is associated with disease progression and mortality. Issue 5 (23rd May 2019) - Mackintosh, John A.; Desai, Sujal R.; Adamali, Huzaifa; Patel, Kinesh; Chua, Felix; Devaraj, Anand; Kouranos, Vasilis; Kokosi, Maria; Margaritopoulos, George; Renzoni, Elisabetta A.; Wells, Athol U.; Molyneaux, Philip L.; et al.
In idiopathic pulmonary fibrosis (IPF), the role of gastro-oesophageal reflux (GOR) and its treatment remain unclear [1]. Both acid and non-acid components of GOR contribute to lung inflammation and fibrosis [2, 3]. There are conflicting data on the use of proton pump inhibitors (PPIs) in IPF, which do not act on the non-acid component of GOR and may be associated with higher rates of respiratory infection [4, 5]. Hiatus hernia (HH) is strongly linked to GOR [6] and is common in IPF patients [7]. One previous study pre-dating the era of anti-fibrotic therapy found an association between HH and increased mortality in IPF [8]. However, it did not control for immunosuppressive therapy, at that time routinely used in IPF treatment but now recognised as harmful, thereby limiting the applicability to patients with IPF today. Furthermore, the impact of HH on lung function in IPF has not been reported in any study to date. The WRAP-IPF study, which randomised patients to fundoplication or medical therapy, has generated interest in the role of surgical GOR interventions [9]. Patient selection for WRAP-IPF was dependent on a positive DeMeester score, a measure of acid reflux that has not been examined in relation to IPF outcomes. We aimed to assess the impact of HH and acid reflux as measured by DeMeester score in IPF, hypothesising that HH, which is associated with both acid and non-acid GOR, may be an important contributor to IPF progression. For IPF patients, the presence of hiatus hernia is associated with lung function decline and increased mortality. This observation supports the view that hiatus hernia may influence pathogenic mechanisms involved in IPF disease progression. http://ow.ly/hPAY30omE9o